2019
DOI: 10.1111/mila.12257
|View full text |Cite
|
Sign up to set email alerts
|

Mind–Language = ? The significance of non‐verbal autism

Abstract: The possibility and extent of thought without language have been subject to much controversy. Insight from nonor minimally verbal humans can inform this debate empirically. Since most such individuals are on the autism spectrum, of which they make up a sizable 25-30%, an important connection between language and autism transpires. Here we propose a model which makes sense of this link and explains why the non-verbal human mind, as present evidence suggests, represents a fundamentally different cognitive phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 140 publications
(174 reference statements)
0
24
0
Order By: Relevance
“…Our findings highlight the fact that many minimally verbal autistic preschoolers have visual and adaptive abilities in the normal range, and risk being underestimated when using solely MSEL global scores. These results also go against the belief that the severity of language deficits in autism would inevitably reflect on non‐verbal/visual abilities (as suggested by Hinzen et al, 2019). But most importantly, our results highlight how the choice of measurement tool contributes to the results we get, and therefore impacts on the research results and the beliefs conveyed in the community regarding the comorbidity between GDD and ASD diagnoses.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Our findings highlight the fact that many minimally verbal autistic preschoolers have visual and adaptive abilities in the normal range, and risk being underestimated when using solely MSEL global scores. These results also go against the belief that the severity of language deficits in autism would inevitably reflect on non‐verbal/visual abilities (as suggested by Hinzen et al, 2019). But most importantly, our results highlight how the choice of measurement tool contributes to the results we get, and therefore impacts on the research results and the beliefs conveyed in the community regarding the comorbidity between GDD and ASD diagnoses.…”
Section: Discussionmentioning
confidence: 51%
“…Such testing challenges may lead to negatively biased estimates of their intellectual level (Akshoomoff, 2006; Courchesne et al, 2015; Courchesne et al, 2019), especially in minimally or nonverbal autistic children who constitute an important proportion of preschool autistic children (from 62% to 77% before age 3, and from 25% to 50% between 3 and 5 years: Anderson et al, 2007; Magiati et al, 2011; Norrellgen et al, 2014; Pickles et al, 2014; Rose et al, 2016; Wodka et al, 2013; Yoder et al, 2014). Because of their language difficulties and testing challenges, these children are often seen as intellectually disabled (Hinzen et al, 2019). Yet, Bal et al (2016) demonstrated that about half of their sample of minimally verbal autistic children had higher nonverbal IQ than predicted by their verbal abilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with aphasia with inner speech deficits, as determined by a silent rhyming task (though perhaps not the best metric), can categorise as well as controls which visual objects go together, but are unreliable in their metacognitive judgments about their categorisations (Langland-Hassan et al, 2017). These findings are supported by studies of people with non-or minimally verbal autism who are also impaired on nonverbal tasks, which the authors in one review HOLISTIC Model 17 feel 'fundamentally questions the idea of the language-independence of thought in humans' (Hinzen et al, 2020).…”
Section: Holistic Model 16mentioning
confidence: 97%
“…The search of ‘thought independent of language’ can only partially be accomplished by looking at early stages of language development, for the reasons just given, and the same applies to adults whose language faculty becomes inaccessible in verbal shadowing tasks. As argued in Hinzen et al. (2019) , however, a potentially more powerful source of insight comes from school-age children with neurodevelopmental disorders, who do not develop language in either production or comprehension at all.…”
Section: Introductionmentioning
confidence: 99%